Transformasi Konsep Mahabbah dalam Sastra Profetik: Studi Kasus Pada Puisi-Puisi Karya Kuntowijoyo - Heri Isnaini (Universitas Palangka Raya, 2026)
The concept of mahabbah (divine love) is one of the pinnacles of achievement in the Sufism tradition that marks the existential closeness between man and God. In the context of prophetic literature, this concept is not only present as an individual spiritual experience, but also undergoes a transformation into a communicative aesthetic and ethical discourse. This study aims to examine the transformation of the concept of mahabbah in Kuntowijoyo's poems by placing them in a prophetic literary framework that emphasizes the dimensions of transcendence, humanization, and liberation. The method used is literary hermeneutics with an interpretive approach to uncover the layers of symbolic meaning in the text. The data is in the form of selected poems that represent the themes of spirituality, Divine love, and human relationship with God. The results of the study show that the concept of mahabbah in Kuntowijoyo's poems undergoes a transformation from the concept of classical Sufism which is esoteric in nature to a more contextual and communicative symbolic expression. This transformation is seen through the use of symbols of love, longing, sincerity, and sacrifice that represent not only man's vertical relationship with God, but also a horizontal relationship with fellow humans. Thus, mahabbah in prophetic literature does not stop at the mystical dimension, but moves towards social praxisis oriented towards human values. This research confirms that poetry functions as a dialectical medium between spiritual experience and social reality, as well as a means of transforming transcendental values into concrete life.